Different roles of two gamma-tubulin isotypes in the cytoskeleton of the Antarctic ciliate Euplotes focardii: remodelling of interaction surfaces may enhance microtubule nucleation at low temperature. - Marziale, Francesca; Pucciarelli, Sandra; Ballarini, Patrizia; Melki, Ronald; Uzun, Alper; Ilyin, Valentin A; Detrich, H W; Miceli, Cristina (FEBS Journal, 2008)
International audience Gamma-tubulin belongs to the tubulin superfamily and plays an essential role in the nucleation of cellular microtubules. In the present study, we report the characterization of gamma-tubulin from the psychrophilic Antarctic ciliate Euplotes focardii. In this organism, gamma-tubulin is encoded by two genes, gamma-T1 and gamma-T2, that produce distinct isotypes. Comparison of the gamma-T1 and gamma-T2 primary sequences to a Euplotesgamma-tubulin consensus, derived from mesophilic (i.e. temperate) congeneric species, revealed the presence of numerous unique amino acid substitutions, particularly in gamma-T2. Structural models of gamma-T1 and gamma-T2, obtained using the 3D structure of human gamma-tubulin as a template, suggest that these substitutions are responsible for conformational and/or polarity differences located: (a) in the regions involved in longitudinal 'plus end' contacts; (b) in the T3 loop that participates in binding GTP; and (c) in the M loop that forms lateral interactions. Relative to gamma-T1, the gamma-T2 gene is amplified by approximately 18-fold in the macronuclear genome and is very strongly transcribed. Using confocal immunofluorescence microscopy, we found that the gamma-tubulins of E. focardii associate throughout the cell cycle with basal bodies of the non-motile dorsal cilia and of all of the cirri of the ventral surface (i.e. adoral membranelles, paraoral membrane, and frontoventral transverse, caudal and marginal cirri). By contrast, only gamma-T2 interacts with the centrosomes of the spindle during micronuclear mitosis. We also established that the gamma-T1 isotype associates only with basal bodies. Our results suggest that gamma-T1 and gamma-T2 perform different functions in the organization of the microtubule cytoskeleton of this protist and are consistent with the hypothesis that gamma-T1 and gamma-T2 have evolved sequence-based structural alterations that facilitate template nucleation of microtubules by the gamma-tubulin ring complex at cold ...